2012
DOI: 10.1371/journal.pone.0041289
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Associated Polymyalgia Rheumatica. An Analysis Using WHO Global Individual Case Safety Database: A Case/Non-Case Approach

Abstract: Objective To assess whether there is an association between statin use and the occurrence of polymyalgia rheumatic (PMR) in the spontaneous reporting database of the World Health Organisation (WHO). Methods We conducted a case/non-case study based on individual case safety reports (ICSR) in the WHO global ICSR database (VigiBase). Case reports containing the adverse event term polymyalgia rheumatica (WHOART or MedDRA Preferred Term) were defined as cases. Non-cases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Several organizations maintain their own well-organized databases of spontaneously reported adverse events, and use them to analyze associations with drugs. The WHO Programme for International Drug Monitoring, starting in 1968, is a cornerstone of world-wide pharmacovigilance, and the Uppsala Monitoring Centre, Uppsala, Sweden, maintains the WHO Global Individual Case Safety Report Database, VigiBase 81-84. In France, pharmacovigilance activities are carried out by 31 regional centers based in clinical pharmacology departments of university hospitals 85, 86, and the French Pharmacovigilance Database has been used to analyze the safety profiles of various drugs 87-91.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Several organizations maintain their own well-organized databases of spontaneously reported adverse events, and use them to analyze associations with drugs. The WHO Programme for International Drug Monitoring, starting in 1968, is a cornerstone of world-wide pharmacovigilance, and the Uppsala Monitoring Centre, Uppsala, Sweden, maintains the WHO Global Individual Case Safety Report Database, VigiBase 81-84. In France, pharmacovigilance activities are carried out by 31 regional centers based in clinical pharmacology departments of university hospitals 85, 86, and the French Pharmacovigilance Database has been used to analyze the safety profiles of various drugs 87-91.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Several case/non-case studies showed that statins might have been significantly associated with an increased risk of polymyalgia rheumatica (n = 327 cases; reporting odds ratio (ROR) 14.21) [69], rheumatoid arthritis (n = 508 patients; adjusted OR = 1.71, p = 0.007; a trend between the potency of statin treatment and the risk of RA was observed) [70] and lupus erythematosus (OR = 1.67) [71]. In the last study [71] cases were defined as drug-induced lupus reports.…”
Section: Rheumatic Diseases and Statin Intolerancementioning
confidence: 99%
“…In Takayasu disease the use of antiplatelet treatment could be protective for ischemic events. Cumulative meta-analysis (6 retrospective studies, 914 pts), monocentric retrospective evaluation (48 pts), retrospective analysis (297 pts) [ 101 - 104 ] …”
Section: Introductionmentioning
confidence: 99%
“…A retrospective recent study has shown that patients using statins were less likely to develop GCA compared to patients not using them [ 103 ]. Interestingly, a recent association study performed using the World Health Organization database, has suggested that the occurrence of PMR could be correlated with statin use [ 104 ].…”
Section: Introductionmentioning
confidence: 99%